Effect of Infused Water Pineapple Cayenne (Ananas Comosus L Merr) on Reducing Uric Acid Levels in Patients With Gout Arthritis - Kadafi, Amirul; Nelyanti, Dian Apri (Poltekkes Kemenkes Banjarmasin, 2024)
The most common disease in old age and is considered a disease that is generally recognized by the public is gout. An increase in uric acid levels is indicated by rheumatic pain in the joints, pain, redness and swelling. Efforts to search and develop medicines to treat rising uric acid levels continue. One alternative that can reduce uric acid levels is to consume cayenne pineapple-infused water. To determine the effect of cayenne pineapple-infused water on uric acid levels in gout arthritis sufferers. Using a quasi-experimental design with a control group with a sample of 44 respondents. Data analysis used univariate and bivariate analysis. Based on the characteristics of the respondents, it was found that (52.2%) were aged 45-59, female (43.2%), had at least secondary school education (50.0%), worked as a labourer (43.2%) and acid levels. mean pre-intervention urate 8.08 mg/dL, post-intervention means 5.01 mg/dL pre-control mean 8.20 mg/dL, post-control mean 8.02 mg/dL, Mann Whitney test results Posttest uric acid in the intervention group had a mean value of 11.50 mg/dL, in the control group the mean value was 33.50 mg/dL. This study found that in the intervention group, the p-value was 0.000 < 0.05. Shows that there is an effect of giving cayenne pineapple-infused water on uric acid levels in gouty arthritis sufferers.